The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1371/journal.pone.0017621
|View full text |Cite
|
Sign up to set email alerts
|

Early T Cell Signalling Is Reversibly Altered in PD-1+ T Lymphocytes Infiltrating Human Tumors

Abstract: To improve cancer immunotherapy, a better understanding of the weak efficiency of tumor-infiltrating T lymphocytes (TIL) is necessary. We have analyzed the functional state of human TIL immediately after resection of three types of tumors (NSCLC, melanoma and RCC). Several signalling pathways (calcium, phosphorylation of ERK and Akt) and cytokine secretion are affected to different extents in TIL, and show a partial spontaneous recovery within a few hours in culture. The global result is an anergy that is quit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 33 publications
9
72
0
Order By: Relevance
“…In the presence of PD-L1 expression on aAPCs, we observed a clear inverse correlation between the level of PD-1 expression and the number of T cells fluxing Ca . These studies are consistent with the notion that PD-1 ligation can interfere with the most membrane-proximal signaling events (32) and clearly demonstrate that the ability of PD-L1-expressing aAPCs to inhibit Ca 2+ is directly proportional to the amount of PD-1 on the T-cell surface.…”
Section: Pd-1 Inhibits Casupporting
confidence: 88%
“…In the presence of PD-L1 expression on aAPCs, we observed a clear inverse correlation between the level of PD-1 expression and the number of T cells fluxing Ca . These studies are consistent with the notion that PD-1 ligation can interfere with the most membrane-proximal signaling events (32) and clearly demonstrate that the ability of PD-L1-expressing aAPCs to inhibit Ca 2+ is directly proportional to the amount of PD-1 on the T-cell surface.…”
Section: Pd-1 Inhibits Casupporting
confidence: 88%
“…Three weeks after induction of complete chimerism, we checked the residual host-type T cells regarding surface marker changes related to T cell anergy such as upregulation of PD-1 and downregulation of IL-7Ra (27)(28)(29), surface marker changes related to apoptosis such as upregulation of FAS (34), and surface marker changes related to T cell exhaustion such as upregulation of TIM-3 (35,36). We found that, although there was no significant difference between host-type T cells from recipients given TCD-BM from MHC II 2/2 mismatched or MHC-matched donors, the host-type T cells from recipients given TCD-BM from MHC-mismatched WT donors upregulated PD-1 expression (p , 0.01; Fig.…”
Section: Mhc-mismatched Complete Chimerism Induces Tolerance Of Pre-ementioning
confidence: 99%
“…The residual host-type T cells in the MHC-mismatched complete chimeras appeared to be anergic with upregulation of PD-1 and downregulation of IL-7Ra. Anergic T cells were reported to upregulate PD-1 and downregulate IL-7Ra (27)(28)(29).…”
mentioning
confidence: 99%
“…B7-H1 molecules expressed on tumor cells play a crucial role in tumor evasion from cytotoxic T lymphocyte (CTL)-mediated immune surveillance through PD-1 (9,10). Tumor-associated B7-H1 delivers an inhibitory signal to tumor-specific CTLs via the B7-H1-PD-1 interaction, resulting in T-cell apoptosis in vitro and in vivo, and the B7-H1-PD-1 interaction attenuates activated tumor-infiltrating T cells through the inhibition of T-cell receptor (TCR) signaling (1,4,11,12). We previously demonstrated that B7-H1-positive myelodysplastic syndrome blasts have a greater ability to induce T-cell apoptosis compared with B7-H1-negative blasts, through the B7-H1-PD-1 pathway (3).…”
Section: Introductionmentioning
confidence: 99%